Non-doped solid-state white light-emitting electrochemical cells employing the microcavity effect. Issue 10 (13th February 2015) - Lin, Guan-Rung; Chen, Hsiao-Fan; Shih, Hsien-Chang; Hsu, Jia-Hong; Chang, Yi; Chiu, Chih-Hung; Cheng, Chia-Yu; Yeh, Yun-Shiuan; Su, Hai-Ching; Wong, Ken-Tsung
Abstract : White electroluminescence can be obtained in non-doped light-emitting electrochemical cells (LECs) by employing the microcavity effect. Abstract : Solid-state white light-emitting electrochemical cells (LECs) have attracted research attention owing to their advantages of simple device structure, low operation voltage and compatibility with solution processes. In this work, we demonstrate a simple approach to obtain white electroluminescence (EL) from non-doped LECs based on a blue-emitting complex. With a relatively thicker emissive layer, red emission can be additionally enhanced by the microcavity effect when the recombination zone moves to appropriate positions. Hence, white EL can be harvested by combining blue emission from the complex and red emission from the microcavity effect. These non-doped white LECs show external quantum efficiencies and power efficiencies up to 5% and 12 lm W −1, respectively. These results show that efficient white EL can be obtained in simple non-doped LECs.